1996
DOI: 10.1053/jhep.1996.v24.pm0008781337
|View full text |Cite
|
Sign up to set email alerts
|

Long-term ethanol administration alters the degradation of acetaldehyde adducts by liver endothelial cells

Abstract: effects of ethanol on liver endothelial cells (LECs). However, Previous reports have shown that long-term ethanolRees et al. 1 have shown recently that the uptake and degradaadministration alters receptor-mediated endocytosis tion of formaldehyde-modified albumin (f-Alb) by the scaven-(RME) of a variety of macromolecules by liver endotheger receptor on LECs is decreased markedly by long-term lial cells (LEC). Acetaldehyde is the major metabolic ethanol consumption. product of ethanol metabolism and has been sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Previous studies by our laboratories have shown that fAlb and AA-Alb are degraded very efficiently by in situ perfused rat livers [5,6,[8][9][10][11][12], and that chronic ethanol consumption impairs this process. Also in these studies, it was possible to show that the removal of KCs by gadolinium chloride did not alter the degradation of f-Alb or AAAlb in situ.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Previous studies by our laboratories have shown that fAlb and AA-Alb are degraded very efficiently by in situ perfused rat livers [5,6,[8][9][10][11][12], and that chronic ethanol consumption impairs this process. Also in these studies, it was possible to show that the removal of KCs by gadolinium chloride did not alter the degradation of f-Alb or AAAlb in situ.…”
Section: Discussionmentioning
confidence: 87%
“…LECs have been shown to bind and degrade formaldehyde and acetaldehyde-modified proteins [8,9,17], and chronic ethanol consumption has been shown to result 6 cells/mL) were incubated at 378 with 125 I-MAA-Alb (25 mg/mL of protein) for the indicated amount of time, aliquots of the cell suspensions (1 mL) were removed, and acid-soluble radioactivity was determined as described in Section 2. Results are expressed as means AE SD (N ¼ 6 in each group), and values significantly different from controls ( in a significant decrease (50-60%) in the ability of LECs to degrade these ligands.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations